2005
DOI: 10.1111/j.1600-0447.2004.00503.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive remediation for adolescents with early onset psychosis: a 1‐year follow‐up study

Abstract: The remediation programme may have a favourable long-term effect for early visual information processing. Improved cognitive functioning in both groups may be caused by beneficial elements in the psychoeducational programme. Because the study may be underpowered, the results should be interpreted with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 45 publications
3
47
1
1
Order By: Relevance
“…Two such issues deserve special consideration: the evaluation of the persistence of remediation effects on cognitive functioning and the assessment of the impact of remediation on functional outcomes. Despite the number of controlled studies of cognitive remediation, only six studies (16,19,21,(28)(29)(30) examined whether improvements in cognitive functioning were maintained at a posttreatment follow-up, precluding the exploration of moderators of treatment effects. The relative lack of data addressing this question may be important because different program, patient, or setting factors could influence the long-term maintenance of cognitive effects compared to short-term effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two such issues deserve special consideration: the evaluation of the persistence of remediation effects on cognitive functioning and the assessment of the impact of remediation on functional outcomes. Despite the number of controlled studies of cognitive remediation, only six studies (16,19,21,(28)(29)(30) examined whether improvements in cognitive functioning were maintained at a posttreatment follow-up, precluding the exploration of moderators of treatment effects. The relative lack of data addressing this question may be important because different program, patient, or setting factors could influence the long-term maintenance of cognitive effects compared to short-term effects.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies also reported cognitive data at follow-up (16,19,21,(28)(29)(30). For these studies, the average effect size at posttreatment was 0.56 (t=4.8, df=5, p<0.001, CI=0.33-0.79; Q=3.4, df=5, n.s.…”
Section: Effects On Cognitive Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Although five previous trials examined the utility of cognitive remediation in patients with major psychiatric disorders, only one of them focused on BD [94][95][96][97][98][99]. The evidence base is currently insufficient to recommend cognitive remediation for wider implementation in BD, although it is possible that it may prove more beneficial for psychosocial functioning than for cognitive rehabilitation [99].…”
Section: Addressing Functional Impairment In Severe Bipolar Disordermentioning
confidence: 97%
“…Additionally, given that people in early schizophrenia experience impairments in cognition and functioning similar or equivalent to those evidenced by individuals in the later stages of their illness, it is thought beneficial to implement CRT as early in the course of illness as possible. Only a handful of studies examining efficacy and durability of CRT in the ARMS 55,56 and FEP 53,54,57,58 have been done to date with early evidence suggesting favourable effects.…”
Section: Cognitive Remediation Therapymentioning
confidence: 99%